Preparing EFL pre-service teachers for curriculum 2013 through authentic materials and assessment integration - Jaelani, Alan; Umam, Amalul (JEES (Journal of English Educators Society), 2021)
Changes in Curriculum lead to changes in teaching and learning processes as well as new ways to demonstrate best practices for increasing students’ achievement. The Curriculum 2013 suggests teachers to use authentic materials and requires them to apply authentic assessments. It is quite challenging for English teachers because this condition creates problems especially for novice teachers. Therefore, they need to have prior knowledge and personal experience related to teaching practice and situation. In this study, authentic materials and authentic assessments were implemented in pre-service-English-teacher classroom at a university in Bogor, specifically in listening class, in order to familiarize them to the kind of materials and assessments. Action research was employed where documentation, observation, questionnaire, and interview were used to collect the data. The result shows that the integration of authentic materials and authentic assessment in EFL classroom helped the students in understanding the nature and the use of authentic materials and authentic assessment for their future needs of profession.